Chad : Poverty Reduction Strategy Paper; 2005 Annual Implementation Progress Report. (IMF Staff Country Reports; Country Report, 2007)
This paper discusses key findings of the National Poverty Reduction Strategy (NPRS) Monitoring and Implementation Report 2005 for Chad. The strategy is based on the attainment of five core objectives: good governance, robust and sustained growth, the development of human capital, improved living conditions for the most vulnerable segments of the population, and environmental protection. This report aims to provide a more comprehensive account of the measures taken and results achieved since the beginning of NPRS implementation.